USE OF CONE BEAM COMPUTED TOMOGRAPHY GRAY SCALE VALUES FOR DIAGNOSING TUMORS AND CYSTS - NASEEM , K; SAEED , U; YASIN , A; SIDDIQI , MA (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Radiology of the hospital from January 2022 to January 2023 to assess the ability of CBCT gray scale value to diagnose tumors and cysts and evaluate differences in bony changes of both. A total of 50 patients were included in the study. CBCT scanner with 68-1073μSv radiation dose was used for obtaining 3D images. Gray scale values were obtained on the tangential section. Radiological diagnosis was made after calculating mean gray values for benign lesions or cysts. Myxoma, odontogenic ghost cell tumor, and the adenomatoid odontogenic tumor had lower grayscale values, and multiple myeloma, cementoblastoma, acanthomatous ameloblastoma, residual cyst, and lateral periodontal cyst had higher values. The mean grayscale value for the tumor was 1468 ± 70.5, and for the cyst was 1292.1 ± 6.5. There was a significant correlation between both (P<0.001). The bone density of normal and pathological maxillofacial regions was compared. The radiolucent area (e.g., axillary sinus) had the lowest, and the radiopaque region (e.g., enamel) had the highest gray scale value. CBCT gray value is a powerful diagnostic tool for tumors, cysts, and other orofacial lesions and has better outcomes than conventional 2-D imaging.